Meningkatkan Kualitas Membaca Al-Qur'an Melalui Literasi Digital Di Desa Perkotaan Kecamatan Secanggang Kabupaten Langkat - Fadhilah Arfa Hasibuan; Atiqoh Hanum; Masithah Ulfah; Tihawa Tihawa; Sri Haryati; Ida Hapni Harahap (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service is a form of active participation in improving social welfare through the application of knowledge and skills to solve problems faced. Urban Village, Secanggang District, Langkat Regency is a division of Karang Gading Village, Secanggang District, Langkat Regency, North Sumatra with a population of 750 people. The programs implemented concentrate on digital education and literacy, as an effort to provide a new atmosphere in teaching and learning methods, especially the use of information and communication technology as a learning medium. This community service activity is carried out with a Community Development approach which is carried out for 10 days. Where children are the main objects in this service. They are taught how to read the Qur'an properly and correctly, and guided with creative and innovative methods, they are directed to read and learn the Qur'an through Gadgets as a medium that contains the Qur'an learning application, ending with submitting their readings through Voice Note. This activity aims for children to be able to utilize and master the use of information and communication technology effectively in the process of learning to read the Qur'an, and the community in Urban Villages can produce quality education, superior and empowered children in the era of globalization.